Neuroimmunology of CNS HIV Infection: A Narrative Review - Meyer, Ana-Claire; Njamnshi, Alfred Kongnyu; Gisslen, Magnus; Price, Richard W. (Frontiers in Neurology, 2022)
This short review provides an overview of the neurobiological interactions of human immunodeficiency virus type 1 (HIV), immune and inflammatory reactions, and CNS injury over the course of infection. Systemic infection is the overall driver of disease and serves as the ‘platform’ for eventual CNS injury, setting the level of immune dysfunction and providing both the HIV seeding and immune-inflammatory responses to the CNS. These systemic processes determine the timing of and vulnerability to HIV-related neuronal injury which occurs in a separate ‘compartment’ with features that parallel their systemic counterparts but also evolve independently. Direct CNS HIV infection, along with opportunistic infections, can have profound neurological consequences for the infected individual. HIV-related CNS morbidities are of worldwide importance but are enhanced by the particular epidemiological, socioeconomic and environmental factors that heighten the impact of HIV infection in Africa.